The ethics of medicai decision-making - Federspil, G.; Macor, C. (Medicina e Morale, 1994)
The article intends to facc thc problem of the relation between scientific knowledge and clinical practice. Medicine is a subject based on knowledge of many biologic phenomena and possibility of modifying them. Therefore it is characterized by theory and technics. As a matter of fact these two aspects are only apparently different, in that technics does not mean to do anything, but an efficient work based on the knowledge of operative practice and with a definitive purpose. The ancient Greeks were the first to wonder why certain events took piace regularly and others did not happen at all: rational knowledge was born. lt finds its full expression in the 17th century and at the same time modern medicine became an applied science which explains the reasons why one has to do certain actions. The authors, after argued the question of ethics in the science, consider the medicine as applied science. Its purpose is to obtain human healthy. Therefore medicai doctor's duties are: 1) to put into practice correctly science, which he professes; 2) to practice medicine to attain its aim. In order to exercise his science properly, a medicai doctor must practice the most consolidated and updated scientific laws, which means to apply the scientific method to medicine.